Social and geographical aspects of the religious sphere development in the Kirovohrad region - Семенюк, Лариса; Сільченко, Юлія (Human Geography Journal, 2017)
The paper dwells on the importance of the social and geographical study of the religious aspects of the society because particularly their development and functioning level influences some social processes in the provinces of the Region. The existing social, economic, historical and geographical factors influencing religious sphere in the Kirovohrad Region have been thoroughly analysed. And historical factor combined with social and geographical position turned out to be the most essential for the formation of religious sphere in the Kirovohrad Region. The researchers provide with the component structure of the religious sphere in the Kirovohrad Region where 37 confessions have been found out as well as 723 registered religious organisations. The authors claim that despite the increase in the number of religious confessions and organisations within the Region it still takes the bottom place in the relevant Ukrainian ranking. Christian denominations dominate in the component structure of the religious sphere in the Kirovohrad Region and make up 96.9 %. The peculiarities of the peculiarities of the religious sphere in the Kirovohrad Region have been defined via calculated coefficients characterising religious environment of the Kirovohrad Region throughout 2001 – 2016. The spatial analysis of the religious and geographical sphere functioning in the districts of the Region have been performed and followed by its main indicators calculation for 2017. It turned out that the highest religious services availability coefficient, the biggest part of religious organisations and the shortest average distance between religious communities have been observed only in two districts, Kirovohrad and Oleksandriia Raions of the Kirovohrad Region.